2004
DOI: 10.1128/iai.72.10.5903-5909.2004
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Acquired Passive Protective Activity against Neisseria meningitidis Group C in the Absence of Serum Bactericidal Activity

Abstract: The hallmark of immunity to meningococcal disease is a bactericidal titer in serum of >1:4 measured with human complement, but this threshold titer may underestimate the extent of protection. We used the infant rat model of meningococcal bacteremia to measure group C passive protective activity in serum samples from 91 unimmunized adults living in California. A total of 35 sera (38.5%) had passive protective activity. Sera with complement-mediated bactericidal titers of >1:4 were 3.4-fold more likely to confer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…meningococcal ACWY-TT vaccine (Nimenrix Ò ), with only 20.6% of healthy toddlers 12 months of age retaining hSBA antibody titers 4 against serogroup A at 1 y after vaccination 33 and only 21.8% of healthy toddlers 12-23 months of age retaining hSBA antibody titers against serogroup A at 3 y after vaccination. 34 Laboratory and assay considerations in assessment of persistence against serogroup A Antibody decay rates also depend on the serological assay used for measurement of antibody titers.…”
Section: Rapid Waning Of Serogroup a Responses After Single Or Multipmentioning
confidence: 99%
“…meningococcal ACWY-TT vaccine (Nimenrix Ò ), with only 20.6% of healthy toddlers 12 months of age retaining hSBA antibody titers 4 against serogroup A at 1 y after vaccination 33 and only 21.8% of healthy toddlers 12-23 months of age retaining hSBA antibody titers against serogroup A at 3 y after vaccination. 34 Laboratory and assay considerations in assessment of persistence against serogroup A Antibody decay rates also depend on the serological assay used for measurement of antibody titers.…”
Section: Rapid Waning Of Serogroup a Responses After Single Or Multipmentioning
confidence: 99%
“…Opsonic activity was found in patients after meningococcal serogroup B infection (19). Also, animal studies have shown that protective activity was associated with high-avidity antibodies (18,20,21). The PorA-specific avidity induced after infection therefore may play an import role in protection.…”
Section: Discussionmentioning
confidence: 98%
“…Other mechanisms therefore may be responsible for induced protection after infection. Recently, several studies have shown protection in infant rat models against meningococcal infection in absence of SBA activity (17,18). The most likely mechanism responsible for protective activity in the absence of SBA is opsonization.…”
Section: Discussionmentioning
confidence: 99%
“…One study indicates that in individuals who had a severe exposure to rabies virus a single booster inoculation 4 years after the initial (post-exposure) treatment was sufficient to maintain a rabies specific antibody titer that would probably confer protection against a second exposure (Fayaz et al, 1981). In another study a threshold titer (with human complement) was found that was likely to confer protection to meningococcal disease (Welsch and Granoff, 2004). In this study protection in the absence of bactericidal activity by complement was associated with significantly higher concentrations and avidities of antibodies directed against a capsular protein of the meningococcus.…”
Section: Article In Pressmentioning
confidence: 99%